The rise and fall of the First International : an interpretation - van der Linden, Marcel (Leiden : E.J. Brill, 1988)
Bibliotheek François Vercammen
Overdruk van Internationalism in the Labour movement 1830-1940
Engels
Brochure
Keywords: Eerste Internationale (1864-1876).